Prevalence and Predictors of malnutrition among elderly in an urban area in Visakhapatnam (India) - Sarada Vadlamani; Sujitha. V; keerthana k; N.G Nagamani; G. Chaitanya; Rashmika I; Manasa R V (Global Journal of Medicine and Public Health, 2024)
Introduction